2017
DOI: 10.1080/0142159x.2017.1301654
|View full text |Cite
|
Sign up to set email alerts
|

Reframing undergraduate medical education in global health: Rationale and key principles from the Bellagio Global Health Education Initiative

Abstract: Global health education (GHE) continues to be a growing initiative in many medical schools across the world. This focus is no longer limited to participants from high-income countries and has expanded to institutions and students from low- and middle-income settings. With this shift has come a need to develop meaningful curricula through engagement between educators and learners who represent the sending institutions and the diverse settings in which GHE takes place. The Bellagio Global Health Education Initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 40 publications
2
35
0
Order By: Relevance
“…One of the main goals of the BGHEI relates to offering curriculum recommendations for global health education . Much can be learned from this review by those who are involved in, or intend to embark on, a global health educational intervention, particularly in terms of preparing students, ensuring time and space for critical reflection and discourse, structuring learning events or experiences to allow for discomfort and a move away from ‘safe’ spaces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main goals of the BGHEI relates to offering curriculum recommendations for global health education . Much can be learned from this review by those who are involved in, or intend to embark on, a global health educational intervention, particularly in terms of preparing students, ensuring time and space for critical reflection and discourse, structuring learning events or experiences to allow for discomfort and a move away from ‘safe’ spaces.…”
Section: Discussionmentioning
confidence: 99%
“…One of the main goals of the BGHEI relates to offering curriculum recommendations for global health education. 111 Much can be learned from this review by those who are involved in, or intend to embark on, a global health educational intervention, particularly in terms of preparing students, ensuring time and space for critical reflection and discourse, structuring learning events or experiences to allow for discomfort and a move away from 'safe' spaces. However, we would argue that the review offers a broader perspective and that addressing the challenges facing health professions education in the 21st century requires a pedagogy of uncertainty that allows for 'human flourishing', acknowledging the complexity of the world we live in and questioning what we believe we know about it.…”
Section: Discussionmentioning
confidence: 99%
“…The ndings of this study demonstrate that GHCR is a promising model for internationally partnered medical schools to utilise for digitally-enabled, student-led, case-based global health learning. The selfreported learning in GHCR aligns favourably with recommended global health learning competencies (7)(8)(9)26). Values considered important in global health are promoted in GHCR, with evidence of formative and transformative learning by some students.…”
Section: Discussionmentioning
confidence: 62%
“…Unprecedented investment by governmental, philanthropic, and academic institutions has decreased the burden of infectious disease, focused attention on non-communicable diseases, supported health service delivery, and advanced the training of physicians and nurses, especially in low- and middle-income countries (LMICs). GHE—defined as clinical health sciences curricula and experiential learning focused on social accountability and rooted in the concepts of equity, cultural sensitivity, and collaborative, interdisciplinary practice of patient- and population-centered healthcare [4]—thrived against this backdrop. An increasingly integrated global economy reinforced cross-national political relationships and the expansion of institutional partnerships supporting GHE.…”
Section: The Era Of Globalism In Which Ghe Programs Developed Has Endedmentioning
confidence: 99%
“…Evidence showed that students from LMICs experience GHE in similar ways to students from HICs, despite their different frames of origin [8]. As a result, GHE increasingly became defined by experiences in “resource-different” settings [4]. For some participants, GHE led to the pursuit of careers involving the principles underlying GH [9].…”
Section: The Era Of Globalism In Which Ghe Programs Developed Has Endedmentioning
confidence: 99%